Mortality Risk Factors of COVID-19 Inpatients at Panembahan Senopati Hospital, Bantul, Yogyakarta - Christiana Sri Wahyuningsih; Esthi Budhi Asih; Ledy Vinantika; Ria Sulistiani (Masters Program in Public Health, 2023)
Background: COVID-19 Case Fatality Rate (CFR) in Bantul district is 2.64%. This figure is higher than the world CFR reported by WHO of 2.07%. Panembahan Senopati Regional General Hospital is a hospital owned by the Regional Government of Bantul Regency and is one of the COVID-19 referral hospitals. This study aims to determine the characteristics and risk factors for the death of inpatient COVID-19 patients at Panembahan Senopati Hospital. Subjects and Method: This type of study is observational analytic with a retrospective cross-sectional design. This research was carried out from July to September 2021 at Panembahan Senopati Hospital. A total of 289 research subjects were selected in total sampling. The dependent variable is the mortality of COVID-19 patients. The independent variables were age, sex, diabetes mellitus, hypertension, chronic renal failure, heart disease, immunological disorders, and chronic liver failure. The data were analyzed by multiple logistic regression. Results: Risk factors for death in hospitalized COVID-19 patients were age, diabetes mellitus, hypertension, and chronic renal failure. Age ≥60 years was 2.13 times more likely to cause death (OR = 2.13; CI 95% = 1.24 to 3.66; p=0.006). Hospitalized COVID-19 patients with comorbid diabetes Mellitus were 2.31 times more likely to cause death (OR= 2.31; CI 95% =1.30 to 4.12; p=0.004). Hospitalized Covid-19 patients with comorbid hypertension 2.18 times chance of causing death (OR= 2.18; CI95% =1.12 to 4.25; p= 0.021). Hospitalized COVID-19 patients with comorbid chronic renal failure were likely to cause 3.25 times the death rate (OR= 3.25; CI 95%= 1.11 to 9.51; p=0.031). Conclusion: Risk factors for death in hospitalized COVID-19 patients are age, diabetes mellitus, hypertension, and chronic renal failure. Keywords: Hospitalization, death, COVID-19 patients Correspondence:Christiana Sri Wahyuningsih. Nursing and Quality Assurance, Panembahan Senopati Hospital. Jl. Dr. Wahidin Sudiro Husodo, Trirenggo, Bantul, Yogyakarta. Email: anachristi19@gmail.com. Mobile: +6281287783924.